2014
DOI: 10.2147/ijn.s61220
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled micelles of novel amphiphilic copolymer cholesterol-coupled F68 containing cabazitaxel as a drug delivery system

Abstract: Despite being one of the most promising amphiphilic block copolymers, use of Pluronic F68 in drug delivery is limited due to its high critical micelle concentration (CMC). In this study, we developed a novel F68 derivative, cholesterol-coupled F68 (F68-CHMC). This new derivative has a CMC of 10 μg/mL, which is 400-fold lower than that of F68. The drug-loading capacity of F68-CHMC was investigated by encapsulating cabazitaxel, a novel antitumor drug. Drug-loaded micelles were fabricated by a self-assembly metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Similar results were formerly noted. 63,64 From the realized results of both DSC and FTIR, we can certify that LX was enclosed within the optimized bilosomal formula.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Similar results were formerly noted. 63,64 From the realized results of both DSC and FTIR, we can certify that LX was enclosed within the optimized bilosomal formula.…”
mentioning
confidence: 77%
“…21,30 It also demonstrates that LX exists in its amorphous state. 63 Fourier Transform Infrared Spectroscopy (FTIR)…”
mentioning
confidence: 99%
“…Pluronic, poly(ethyleneoxide)–poly(propylene oxide)–poly(ethylene oxide) (PEO–PPO–PEO), a water-soluble biocompatible polymer, has been widely used to design drug delivery systems343536. Additionally, researchers suggested that PEO had higher affinity to the surface of the small intestine3738.…”
mentioning
confidence: 99%
“…In the present study, a PLA-PEO-PPO-PEO-PLA (PLA-Pluronic F68-PLA, PLFL) block copolymer was successfully prepared from L-lactide and Pluronic ® F68 using a ring-opening polymerization method. Pluronic, poly(ethyleneoxide)–poly(propylene oxide)–poly(ethylene oxide) (PEO–PPO–PEO), a water-soluble biocompatible polymer, has been widely used to design drug delivery systems 34 35 36 . Additionally, researchers suggested that PEO had higher affinity to the surface of the small intestine 37 38 .…”
mentioning
confidence: 99%
“…Studies have shown that lipopolymers containing a high amount of cholesterol have enhanced tumor distribution in comparison with cholesterol-free carriers. 36 Moreover, the cholesterol-bearing nanoparticles due to the relevance of their aromatic structure to SFB can make a reservoir interacting with the drug through hydrophobic and π-π mechanisms for efficient loading of SFB. Therefore, in the present study, taking the advantages of polycation (i.e.…”
Section: Introductionmentioning
confidence: 99%